Structure Simulation and Study of Electronic and Dielectric Properties of Unfluorinated and Fluorinated 3,4-Dihydroxy-5-(Hydroxymethyl)Proline - Sreepad , H. R. (Asian Journal of Science and Applied Technology, 2017)
First-principles calculations based on Density Functional Theory have been done on the technologically important Proline derivative (3,4-Dihydroxy-5-(hydroxymethyl)(proline) [????6????11????????5]. The triclinic structure of the material has been simulated and the structural parameters are found to be a=4.309Å, b=6.004Å, c=6.967Å, ????=103.47????, ????=103.17????, ????=99.80????. After fluorination the structural parameters are found to be a=4.301Å, b=6.214Å, c=7.113Å, ????=105.10????, ????=104????, ????=97.68????. Electron Density of States (EDOS) has been computed in the material using the Electronic structure calculation code of Quantum-Espresso which gives a Band gap of 4.47 eV. After fluorination the Band gap is found to be 3.34 eV. The value of dielectric constant in the material comes out to be 2.32, 2.70 and 2.61 along x, y and z axes respectively and the average value comes out to be 2.54. After fluorination the dielectric constant of the compound comes out to be be 2.38, 2.56 and 2.56 along x,y and z axes respectively the average value comes to be 2.50. The computed phonon modes range from 101????????−1 to 3157????????−1. After fluorination the phonon modes range from 306????????−1 to 3563????????−1.